The influence of the Teams Games Tournament model with Kokami on student collaboration - Aswiyana, Nur; Puspitasari, Ratna (JIPSINDO, 2024)
The research aims to determine the significant differences in the collaboration skills of class IX students who are taught through the Kokami-mediated tournament games team learning model and groups of students who are taught through conventional learning in Class IX of SMP Negeri 14 Cirebon City. The research method used is a quantitative method with an experimental approach with a Quasi quasi-experimental design research design with a Non-equivalent group design or Control group pretest-posttest design. The population in this study was 155 students, while the sample in this study was 60 students. Data collection methods were carried out through observation, questionnaires and documentation. The data obtained were analyzed using descriptive statistics and inferential statistics with the help of SPSS 22. The research results showed that there were differences in the collaboration skills of students who used the Kokami-mediated tournament team game model with conventional methods. Based on the results of the paired test samples, a significance value of 0.000 was obtained. Because the significant value was < sig level 0.05 and ð‘¡calculated (55.316) > ð‘¡table (1.672) then Ho was rejected, meaning that there was a significant difference between the experimental class post-test and the control class post-test. So it can be concluded that the use of the Kokami-mediated tournament games team learning model influences students' collaboration skills in social studies subjects at SMP Negeri 14 Cirebon City.